Penegakan Sanksi Pidana Dalam Undang-Undang Nomor 24 Tahun 2011 Tentang Badan Penyelenggara Jaminan Sosial (Bpjs) Di Wilayah Hukum Pengadilan Negeri Surakarta - Nugraha, Aditya; , Muchamad Iksan, SH., MH (2016)
This study is proposed to describe criminal law policy, enforcement of sanctions, and abstacles to enforcement of criminal sanctions in law No 24 of 2011 about BPJS in the jurusdiction of district court of Surakarta. The method is used empirical juridical kind of deccriptive analysis research. The data source consists of primary data is result of interviews and secondary data is materials of primary legal, secondary, and tertiary. The method of collecting data is observation and interview. Based on analysis, show that criminal law policy in law No 24 of 2011 contained in Article 54 and 55 abaout imposition of criminal sanctions to criminal acts such as imprisonment and fines. Until now, there are note case related to BPJS in Surakarta. If here are case related to BPJS in Surakarta, there are two step ways imposition criminal law. The first step is given administrative sanctions and second step given criminal sanctions. Surakarta police is inforce law no 24 of 2011 there are abstacles, namely juridical abstacle and non juridical abstacle.